2015
DOI: 10.1515/hukin-2015-0074
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Reliability of a Novel Test of Upper Body Isometric Strength

Abstract: The purpose of the present investigation was to examine the association of a novel test of upper body isometric strength against a 1RM bench press measurement. Forty college age adults (n = 20 female, n = 20 male; age 22.8 ± 2.8 years; body height 171.6 ± 10.8 cm; body mass 73.5 ± 16.3 kg; body fat 23.1 ± 5.4%) volunteered for the present investigation. The participants reported to the lab on three occasions. The first visit included anthropometric measurements and familiarization with both the upper body isom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
(18 reference statements)
1
11
2
Order By: Relevance
“…To our knowledge only one study has investigated the reliability of an isometric pushup in assessing upper-body isometric strength (5). This research showed that an isometric assessment in a push-up position had good within-day reliability (ICC=0.98), with a multiple regression model (r 2 =0.86, p≤0.01) identifying isometric peak force as a significant predictor of one repetition maximum (1RM) bench press (p≤0.01).…”
Section: A C C E P T E Dmentioning
confidence: 93%
See 1 more Smart Citation
“…To our knowledge only one study has investigated the reliability of an isometric pushup in assessing upper-body isometric strength (5). This research showed that an isometric assessment in a push-up position had good within-day reliability (ICC=0.98), with a multiple regression model (r 2 =0.86, p≤0.01) identifying isometric peak force as a significant predictor of one repetition maximum (1RM) bench press (p≤0.01).…”
Section: A C C E P T E Dmentioning
confidence: 93%
“…To our knowledge, there is limited research on the measurement of upper-body isometric strength qualities utilizing a push-up and its relationship to sports specific dynamic performance (5).…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…The test was performed three times with 5 min rest between assessments. The validity and reliability of this test have been reported in the literature [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Isometric strength tests are popular assessments that are widely used to assess maximum force-time curve characteristics of the muscular system for the lower [1][2][3] and upper limbs [4][5][6]. This strength testing method has been shown to be an effective approach for monitoring strength training adaptations, especially in well trained athletes who show only subtle changes even after long period of training [7,8], or to assess acute changes in performance during the recovery phase following high-volume resistance training sessions [9].…”
Section: Introductionmentioning
confidence: 99%